Genetic information in the decision-making process for the training of a high-performance Brazilian swimmer: A case report - Bottura, R. M.; Dentillo, D. B. (Research Square, 2024)
Introduction: Although several genetic variations have been associated with athletic profiles and athletic performance, there is little scientific literature on the incorporation of this information into the planning of daily training, especially in elite athletes. The aim of this study is to present our one-year training experience with a high-performing open water marathon swimmer, integrating insights from genetic information.